2012
DOI: 10.1002/bdra.23092
|View full text |Cite
|
Sign up to set email alerts
|

Moderately high intake of folic acid has a negative impact on mouse embryonic development

Abstract: BACKGROUND:The incidence of neural tube defects has diminished considerably since the implementation of food fortification with folic acid (FA). However, the impact of excess FA intake, particularly during pregnancy, requires investigation. In a recent study, we reported that a diet supplemented with 20-fold higher FA than the recommended intake for rodents had adverse effects on embryonic mouse development at embryonic days (E)10.5 and 14.5. In this report, we examined developmental outcomes in E14.5 embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 38 publications
3
59
0
1
Order By: Relevance
“…In previous murine studies, we observed more developmental delays and heart defects in embryos (17) and more liver damage in adults (16) fed a diet containing 10 times the recommended diet content for folic acid, which is equivalent to current recommendations for high-risk women (3). In light of those findings, we used a diet that contained one-half that amount in the current study to be more relevant to elevated folic acid intakes that are commonly observed in pregnant women (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous murine studies, we observed more developmental delays and heart defects in embryos (17) and more liver damage in adults (16) fed a diet containing 10 times the recommended diet content for folic acid, which is equivalent to current recommendations for high-risk women (3). In light of those findings, we used a diet that contained one-half that amount in the current study to be more relevant to elevated folic acid intakes that are commonly observed in pregnant women (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…MethylTHF rose w1.7-fold in the plasma of mice fed the FASD. In previous studies, we showed that total plasma folate rose w2.5-fold and w10-fold in pregnant mice fed a 103FASD and an FASD with 20-fold the recommended diet content, respectively (17,29). For comparison, total plasma folate was reported to increase 2-fold in women who were taking 1.1 mg folic acid/d and 3.4-fold in women who were taking 5 mg folic acid/d (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that women with the highest quartile folate and the lowest quartile zinc were vulnerable to fetomaternal complications (Mukherjee et al 1984). Recently, it was demonstrated that high-dose folic acid supplements were associated with adverse effects on fetal mouse development (Mikael et al 2013). It was also shown that folic acid supplements (400 lg) given every other day to individuals who were consuming diet providing about 3.5 mg zinc were associated with increased loss of zinc via faces .…”
Section: Possible Clinical Consequencesmentioning
confidence: 99%
“…Так, у потомства самок мышей, полу-чавших диету с дозой фолиевой кислоты, экви-валентной дозе 4 мг/сут у людей, наблюдалось увеличение гибели эмбрионов, задержка эмбрио-нального роста, повышение риска появления по-роков сердца по сравнению с животными, полу-чавшими контрольную диету [25]. Было отмечено значительное увеличение риска развития опухо-лей молочной железы у потомства самок крыс, получавших диету с повышенным в 2,5 раза со-держанием фолиевой кислоты [23].…”
Section: опасения в отношении высокодозной и/или длительной терапии фunclassified